Efektywność i bezpieczeństwo leczenia wysiękowego zwyrodnienia plamki związanego z wiekiem doszklistkowymi iniekcjami bevacizumabu w obserwacji 6-miesięcznej - Figurska, Małgorzata (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
Purpose: To evaluate 6 months follow-up data including the effect on vision and anatomic macular outcome in patients treated with intravitreal bevacizumab for exudative AMD. Bevacizumab is the humanized full-length antibody which was developed to be used to treat metastatic colon and breast cancer. Though not specifically developed for intraocular use, bevacizumab has demonstrated biologic activity akin to ranibizumab or pegaptanib in treatment of exudative age-related macular degeneration (AMD). Intravitreal bevacizumab injections in every case are therapy off-label. Material and methods: Twenty six patients with active, exudative AMD (classic form 20/26 and occult 6/26) received 1.25 mg intravitreal bevacizumab every six weeks (three doses). Ophthalmic evaluation included examination of visual acuity in decimal fraction, log MAR and number of ETDRS letters, ophthalmoscopy, optical coherence tomography and fluorescein angiography. Change in vision and central retinal thickness (CRT) from baseline was evaluated using Anova test. Results: Mean log MAR vision pre-injections was 0.68, after the first injections really improved to 0.55, after the third injection was 0.49 and at 6 months was 0.50. 88% of patients (23/26) maintained improved or stable vision at six months. One case of macular haemorrhage occurred.with significant vision decreased. Vision improved by 15 or more letters was observed in 30% patients (8/26). Mean central retinal thickness pre-injections was 299.23 µm, after the first injection really decreased to 299.23 µm, after the third injection was 282.26 µm, at 6 months was 293.23 µm. No adverse systemic events with one adverse ocular, were observed. Conclusions: Intravitreal bevacizumab with the saturation phase is an effective and good tolerated treatment for wet AMD, resulting in improved vision and foveal anatomy at 6 months follow-up. There is small number of randomized, controlled trial with intravitreal bevacizumab and subsequent observation to formulate optimum scheme of bevacizumab therapy for wet AMD should be done.